2016
DOI: 10.1002/jez.b.22711
|View full text |Cite
|
Sign up to set email alerts
|

Morphological And Molecular Analyses of an Anatomical Novelty: The Pelvic Fin Filaments of the South American Lungfish

Abstract: The pelvic fins of male South American lungfish, Lepidosiren paradoxa, are adorned with a distinctive array of filaments, which grow and become highly vascularized during the breeding season. The resemblance between these pelvic fin filaments (PFFs) and external gills of other vertebrates suggested that this gill-like structure was used for physiological gas exchange. It has been proposed that the unique pelvic fin of male L. paradoxa is used for release of oxygen from its blood into the environment in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, given the overall similarity between pelvic fin filaments and external gills, it was also proposed that pelvic fin filaments were used to aerate the eggs by releasing oxygen from the male’s blood into the water 38 . Recently, however, it was shown that Lepidosiren pelvic fin filaments neither have the morphology compatible for oxygen diffusion nor the gene expression profile typical of gill filaments 39 . Therefore, it is conceivable that GbE may help to extract O 2 from the water to support the development of the embryo, which may be considered analogous to the function of the embryonic Hb in tetrapods 3 .…”
Section: Discussionmentioning
confidence: 99%
“…However, given the overall similarity between pelvic fin filaments and external gills, it was also proposed that pelvic fin filaments were used to aerate the eggs by releasing oxygen from the male’s blood into the water 38 . Recently, however, it was shown that Lepidosiren pelvic fin filaments neither have the morphology compatible for oxygen diffusion nor the gene expression profile typical of gill filaments 39 . Therefore, it is conceivable that GbE may help to extract O 2 from the water to support the development of the embryo, which may be considered analogous to the function of the embryonic Hb in tetrapods 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The function of these fin attachments has not yet been fully clarified. Suggestions that they serve as "limb gills" for the release or uptake of oxygen could not be directly confirmed (Lima et al, 2017).…”
Section: Introductionmentioning
confidence: 98%